A unified theory of the firm from Tawhidic paradigm - Mhd. Sarif, Suhaimi (2013)
This study develops a unified theory of the firm from Tawhidic paradigm for a comprehensive theory to describe the nature of the firm, the scope and boundaries of assessment on organizational environments, and the assessment of internal organizations to formulate, implement and evaluate organizational strategies. The conventional approach to the theory of the firm is not adequate to respond to external, internal, and human dynamism. The market-based theory of the firm emphasises on the industrial organizational perspective only of the firm, which is lack of dynamism. The evolutionary approach into resource-based and knowledge-based of theory of the firm is also unable to provide a unified theory of the firm due to lacks of spirituality foundation to sustain intellectual contribution from knowledge workers. As an alternative, this study proposes a unified theory of the firm the Tawhidic paradigm approach as a mean to achieve organizational sustainable innovation and competitive advantage. The study used qualitative method via personal interview 15 senior managers of Islamic financial institutions that listed in Bursa Malaysia about the nature of the firm, the scope and boundaries of the companies that contribute to a unified theory of the firm. The informants argued that the vision, mission and objective statements that differentiate the shari’ah compliant and non-shari’ah compliant companies. The shariah-compliant companies apply Tawhidic paradigm in terms of companies’ continuous improvement in all functional aspects, value added services to the stakeholders, and enhancing social welfare to the humanity. The use of qualitative method through personal interviews is appropriate for exploratory nature of the study to develop a unified theory of the firm. Nevertheless, the findings cannot be generalizable. Theoretical contribution from this study is the development of framework of the theory of the firm from Tawhidic paradigm, which adds into the sustainability principles and business continuity. In terms of policy implications, the study provides significant insights to business decision makers and economic policy makers to subscribe Tawhidic paradigm for sustainable economic growth and national prosperity.